PROSPEK PENGEMBANGAN USAHATANI TUMPANGSARI TANAMAN PANGAN; SINGKONG (Manihot esculenta) DAN JAGUNG (Zea mays) DENGAN TANAMAN LAIN DI KECAMATAN SEMIN, KABUPATEN GUNUNGKIDUL - Hendra Ginting; Ari Astuti (Fakultas Pertanian UST, 2018)
This research was conducted in Sumberejo, Semin, Gunungkidul. The purpose of this research is to analyze the income of intercropping farming system; to analyze the feasibility of income farming system pattern of farming; and to know the ideal intercropping cropping pattern. The method of determining the research area was conducted purposive while in the sampling method using simple random sampling with 60 respondents were 30 farmers intercropping cassava-corn-soybeans and 30 farmers intercropping cassava-corn-peanut. Data analysis method used is income analysis and feasibility analysis with hypothesis testing using t test. The results showed that the income of intercropping cassava-corn-soybean is Rp 4,500,555,02/farm while the income is Rp. 10.001.233,38/Ha greater than the income of intercropping farming cassava-corn-peanuts Rp. 1.557.155,67/farm while the income is Rp 3.538.990,21/Ha. While the feasibility analysis showed that the income of intercropping farming cassava-corn-soybean with R/C value equal to 4.01 and intercropping cassava-corn-peanut with value R/C Ratio 2,23. Result of t test between income of intercropping cassava-corn-soybean and intercropping farming cassava-corn-peanut showed that t-count equal to 1,968 and t-table 1,671 with Î± = 0,05 while t test at R / C Ratio with value t -the count of 3.454 and t-table 1.671 with Î± = 0.05. And the ideal cropping pattern is intercropping of cassava - corn - soybeans in review of 4 aspects: financial aspect, production aspect, marketing aspect and social aspect.